How Could Carbon Credits for Reducing Deforestation Compete with Returns from Palm Oil: A Proposal for a More Flexible REDD Valuation Tool - Morel, Alexandra C; Morel, Benoit F (Journal of sustainable forestry, 2012)
In order for carbon credits awarded for reducing emissions from deforestation and degradation of forests (REDD) to be effective, they need to be competitive with alternative land uses. In the case of Southeast Asia, oil palm cultivation is one of the most lucrative possible land uses. Existing mechanisms for awarding certified emission reductions (CERs) might not be adequately flexible to changing commodity prices or to meet the needs of landowners who heavily discount future returns from their land. Real options could be a useful valuation tool for negotiating an annual contract that guarantees a minimum payment or “strike price” to the landowner depending on the potential returns from cultivation of their land. The real option based algorithm computes a competitive payment dependent on the relevant commodity prices contributing to land cover change. This article proposes a method whereby the risk is shared between the seller and buyer, providing a per hectare payment that favors the conservation of forests containing higher biomass per hectare.